Reflections of a Chinese Academic Mom Struggling to Survive a Pandemic - Ma, Catherine (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
Each of us has been negatively affected by this pandemic, but mothers have had to shoulder the brunt of it, as they have been forced to work from home, provide child/elder care, and ensure that their family survives. Sadly, academic mothers have been burdened not only with an increased workload at home but also with trying to juggle their academic careers, which have been gravely affected by this pandemic. As a Chinese academic mother, I have struggled with managing my publishing requirements, my service to my department, and my online teaching responsibilities. I have had to care for elderly family members, who are more susceptible to COVID-19, and for my children, who have been exposed to COVID-19. I have also had to work through filial piety failures as a daughter and daughter-in-law. Sharing the struggles of academic mothers aims to expose how the exorbitant workload that falls upon academic mothers is not sustainable and to address systemic problems that have been long plagued both the academic and home environment. All mothers cannot continue to support a system or a government that lacks leadership during global crises that do not value the visible and invisible labor of mothers because women have far too long been viewed as disposable. In sharing my experiences during this pandemic as a Chinese mother and academic navigating through this uncharted territory of pandemic survival, I hope my journey can provide support to other academic mothers as we advocate for structural change in how mothers should be supported as essential workers.